Molecular Simulation of B-Cell Epitope Mapping from Nipah Virus Attachment Protein to Construct Peptide-Based Vaccine Candidate: A Reverse Vaccinology Approach - Kharisma, Viol Dhea; Dian, Farida Aryani; Burkov, Pavel; Scherbakov, Pavel; Derkho, Marina; Sepiashvili, Ekaterina; Sucipto, Teguh Hari; Parikesit, Arli Aditya; Murtadlo, Ahmad Affan Ali; Jakhmola, Vikash; Zainul, Rahadian (Makara Journal of Science, 2023)
There are no specific drugs or vaccines for Nipah virus (NiV), which is a new Paramyxovirus that infects swine and humans. This study was conducted to investigate B-cell epitope mapping of the NiV attachment glycoprotein and to construct peptide-based vaccine candidates using the reverse vaccinology approach. To generate the linear B-cell epitope, the NiV isolates were extractad from GenBank, NCBI, using the IEDB web server; peptide modeling was conducted using PEP-FOLD3; docking was conducted using PatchDock and FireDock; and in silico cloning was designed using SnapGene. Various peptides were successfully identified from the NiV attachment glycoprotein based on B-cell epitope prediction, allergenicity prediction, similarity prediction, and toxicity prediction. An in silico cloning design of the pET plasmic was also developed. The peptide “RFENTTSDKGKIPSKVIKSYYGTMDIKKINEGLLD” (1G peptide) is predicted to be a potential candidate for the NiV vaccine as it has several good vaccine characteristics. It increases the immune response of B cells through activation, differentiation into plasma cells, the formation of memory cells, and it may increase IgM/IgG antibody titres for viral neutralization. However, the results of this study should be further verified through in vivo and in vitro analyses